Sales Imporvement towards Digital Marketing in COVID-19 Pandemic - Kurniawan, Gogi; Heridiansyah , Jefri (International Journal of Social Science and Business, 2024)
The Covid-19 pandemic, which began in early 2020 and was followed by restrictions prohibiting community activities and imposing stringent oversight, has severely impacted nearly all sectors of trade, particularly managers of micro and small businesses, also known as MSMEs. This study is explanatory in nature. The sampling method used was purposive sampling, selecting 74 MSME managers. Paired t-test analysis of the differences shows that the probability of increased sales volume through digital marketing media is greater than that of conventional marketing media. Additionally, the level of consumer response to MSMEs is higher when using digital marketing compared to conventional methods, and the intensity of interaction between MSME marketers and consumers is greater when using digital marketing media. The results of this study also demonstrate that the opportunity for MSMEs to promote or re-market products to potential consumers through digital marketing media is greater than for MSMEs still relying on conventional marketing methods.